Chronic stress triggers divergent dendritic alterations in immature neurons of the adult hippocampus, depending on their ultimate terminal fields - Dioli, C.; Patrício, P.; Sousa, N.; Kokras, N; Dalla, C; Guerreiro, S.; Santos-Silva, M. A.; Rego, A. C.; Pinto, L.; Ferreiro, E.; Sotiropoulos, I (Transl Psychiatry, 2019)
Chronic stress, a suggested precipitant of brain pathologies, such as depression and Alzheimer's disease, is known to impact on brain plasticity by causing neuronal remodeling as well as neurogenesis suppression in the adult hippocampus. Although many studies show that stressful conditions reduce the number of newborn neurons in the adult dentate gyrus (DG), little is known about whether and how stress impacts on dendritic development and structural maturation of these newborn neurons. We, herein, demonstrate that chronic stress impacts differentially on doublecortin (DCX)-positive immature neurons in distinct phases of maturation. Specifically, the density of the DCX-positive immature neurons whose dendritic tree reaches the inner molecular layer (IML) of DG is reduced in stressed animals, whereas their dendritic complexity is increased. On the contrary, no change on the density of DCX-positive neurons whose dendritic tree extends to the medial/outer molecular layer (M/OML) of the DG is found under stress conditions, whereas the dendritic complexity of these cells is diminished. In addition, DCX+ cells displayed a more complex and longer arbor in the dendritic compartments located in the granular cell layer of the DG under stress conditions; on the contrary, their dendritic segments localized into the M/OML were shorter and less complex. These findings suggest that the neuroplastic effects of chronic stress on dendritic maturation and complexity of DCX+ immature neurons vary based on the different maturation stage of DCX-positive cells and the different DG sublayer, highlighting the complex and dynamic stress-driven neuroplasticity of immature neurons in the adult hippocampus.
Keywords: Animals; Dendrites/*pathology; Dentate Gyrus/pathology; Doublecortin Protein; Hippocampus/*cytology/physiopathology; Male; Mice; Mice, Inbred C57BL; Microtubule-Associated Proteins/physiology; Neurogenesis; Neuronal Plasticity; Neurons/*pathology; Stress, Psychological/*physiopathology